2012
DOI: 10.1074/jbc.m112.393561
|View full text |Cite
|
Sign up to set email alerts
|

Annexin-1-mediated Endothelial Cell Migration and Angiogenesis Are Regulated by Vascular Endothelial Growth Factor (VEGF)-induced Inhibition of miR-196a Expression

Abstract: Background: Annexin-A1 is an important regulator of VEGF-mediated endothelial cell migration and angiogenesis. Results: We found that miR-196a targets Annexin-A1 to inhibit VEGF-mediated cell migration and angiogenesis. Moreover, VEGF decreases miR-196a and increases Annexin-A1. Conclusion: VEGF-induced decrease of miR-196a expression may participate to the angiogenic switch. Significance: These results bring important new insights in understanding the mechanisms underlying angiogenesis-associated pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 49 publications
4
60
0
1
Order By: Relevance
“…ANXA1 has been shown to regulate the migration of many kinds of cells, such as neutrophils [27] and endothelial cells [28]. ANXA1 was also found to play critical roles in the engulfment and phagocytosis of apoptotic cells [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…ANXA1 has been shown to regulate the migration of many kinds of cells, such as neutrophils [27] and endothelial cells [28]. ANXA1 was also found to play critical roles in the engulfment and phagocytosis of apoptotic cells [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…17 Activation of annexin A1 is involved in vascular endothelial growth factor-induced endothelial migration. 23 Overexpression of calreticulin blocks trophoblast migration. 24 It is now accepted that progesterone provides a better environment for endometrial remodeling by inducing endothelial migration and new vessel formation in decidual tissues.…”
Section: Progestrone Anti-inflammatory Proteins and Cytoskeletonmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is another important factor regulating angiogenesis, and angiogenesis is important in tumour growth and metastasis. Pin et al [22] found that VEGF-induced cell migration and angiogenesis of miR-196a can change the expression level of ANXA1, which is controlled by p38-ANXA1 signal conduction pathway. The function of Helicobacter pylori (H. pylori) infection in GC has also been demonstrated, showing that H. pylori can change the cellular ANXA1 localization [23] .…”
Section: Discussionmentioning
confidence: 99%